2020
DOI: 10.1016/j.sjbs.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on baseline susceptibility and stability of insecticide resistance against Plutella xylostella (Lepidoptera: Plutellidae) in the absence of selection pressure

Abstract: Plutella xylostella L. (Lepidoptera: Plutellidae) is an important pest causing significant losses to vegetables worldwide. Insecticides resistance in P. xylostella is a serious issue for scientists since last 30 years. However, deltamethrin and Bt Cry1Ac are commonly used insecticides against P. xylostella but studies involving development of resistance in P. xylostella against these two insecticides at different temperatures are lacking. The current study was aimed to find out the toxicity of deltamethrin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…An early oviposition (egg laying) period under the selection pressures of a specific diet, may result in an increased metabolic rate, as reported in previous investigations [10,21,61,91]. The highest lifetime fecundity (overall oviposition per female) was observed with 10 eggs of P. gossypiella in our study (Table 3), which showed the egg laying potential of O. strigicollis with specific diets, in correlation to previous studies [14,17,18,30,33,49,54,81,92].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…An early oviposition (egg laying) period under the selection pressures of a specific diet, may result in an increased metabolic rate, as reported in previous investigations [10,21,61,91]. The highest lifetime fecundity (overall oviposition per female) was observed with 10 eggs of P. gossypiella in our study (Table 3), which showed the egg laying potential of O. strigicollis with specific diets, in correlation to previous studies [14,17,18,30,33,49,54,81,92].…”
Section: Discussionsupporting
confidence: 91%
“…This showed that O. strigicollis had greater reproduction potentials on the higher prey densities (10 and 15 eggs of P. gossypiella), enabling it to complete its development faster. Previous studies on the dipteran and lepidopteran insects have shown the same trends of results [11,61,76], that the reproduction rate and expectancy of the individuals was affected by the availability of the prey pressure and environmental factors, e.g., temperature.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Culture was maintained on P. gossypiella eggs in the laboratory according to a previously described method ( Zhou et al, 2006 ). The population of O. strigicollis was maintained on the P. gossypiella eggs at three temperatures (24, 28 and 32 °C) to acclimatize for at least two generations before the experiments ( Jaleel et al, 2020 ). The reason for the selection of three temperatures (24, 28 and 32 °C) was that many Orius spp.…”
Section: Methodsmentioning
confidence: 99%
“…The biology of predators and parasitoids is greatly influenced by environmental factors ( Jaleel et al, 2019 ; Ali et al, 2020 ). Temperature is one of the most important abiotic environmental factors ( Saleh & Sengonca, 2003 ; Jaleel et al, 2020 ). The development time of insect pests is greatly affected by variable temperature ( Barbosa et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%